"Closer to the Unfair Reality": Magnitude and Spatial Analysis of Femicides in Ecuador. Issue 17 (September 2021) - San Sebastián, Miguel; Vives-Cases, Carmen; Goicolea, Isabel
During the last 5 years, Ecuador has published a series of progressive laws aiming to protect girls and women against any type of violence. While these efforts are of extreme importance, concerns were raised by national nongovernmental organizations that the official numbers might be biased due to the restricted definition of femicide applied. The main objective of this study was to assess the magnitude and spatial distribution of the femicide rate by province in Ecuador in 2017. Data on cases were collected by a national network of nongovernmental organizations. Age-specific population data were obtained from the National Institute of Statistics for the year 2017. Thematic maps of overall and age-specific femicide rates were also constructed. Moran's index was used to identify clusters of provinces with similar risks for the occurrence of the outcome. The total number of femicides during 2017 was 155, but age could not be recorded in 9 of those cases. More than one-third of the cases (36.99%) occurred in young women aged 15 to 24 years. The total rate was 1.99/100, 000 women. When the femicide definition was restricted to women 15 years and above, the total rate increased to 2.41 cases/100, 000. The femicide rate in Orellana boosted to 10.21 cases/100, 000 in the age group of 15 years and older, the highest in the country. No pattern of spatial autocorrelation was observed. Femicides in Ecuador is a big public health problem, particularly in certain Amazon provinces. The observed rate for women above the age of 15 years (2.41) places Ecuador among the countries in the Latin American and the Caribbean region with the highest femicide rates. While progressive policies have been implemented in the last years, more educational interventions are needed at all societal levels to eradicate this kind of violence.